Contamination, ecological, and human health risks of heavy metals in water from a Pb-Zn-F mining area, North Eastern Nigeria - Adeniyi JohnPaul Adewumi; Temitope Ayodeji Laniyan (IWA Publishing, 2023)
In Nigeria, artisanal mining has become a serious issue. In the Nigerian mining region of Arufu Pb-Zn-F, this study assessed the level of pollution, ecological hazards, and health risks related to the presence of metals in the water. In the dry and rainy seasons, 36 water samples (20 from the ground, 10 from the surface, and six from the mine) were gathered. Samples were examined for the presence of heavy metals such as Cr, Co, Ni, Cu, Zn, As, Cd, and Pb. Other than Cu, Zn, As, Cd, Sb, and Cd (surface water, dry season), which were below the acceptable norm, all water samples had metals over the suggested limits. Heavy metals from nearby mining activities polluted the water, according to contamination evaluations utilizing the contamination factor (CF). Metals in the water may pose very significant ecological dangers, according to ecological risk assessments. The evaluation of human health risks revealed that both adults and children in the region are susceptible to carcinogenic and non-carcinogenic health hazards since the hazard index (HI) values for both indices were above 1 × 10−5 and above 1, respectively. This report emphasizes the need for monitoring mining operations in the nation to safeguard public health. HIGHLIGHTS Metal pollution of Nigeria's water is severe owing to mining activity.; The major contributors are toxic metals, including Cr, Co, Ni, Cu, Zn, As, Cd, Pb, and Fe.; Metals in the water pose high ecological risks in the area.; The total HQ and HI values of metals for both oral and dermal intake were greater than 1.; Results indicate that residents of this area, including children and adults, are susceptible to both carcinogenic and non-carcinogenic health issues.;